The Effect of Administrative Decision Support Systems in Improving the Quality of Administrative Decisions in Syrian Universities. (Field study at Tishreen University) - سليمان, حيان (Latakia University Journal -Biological Sciences Series, 2023)
The study aimed to determine the impact of administrative decision support systems in improving the quality of administrative decisions, and the researcher relied on the deductive approach as a general methodology for research and following the survey methodology. The ability of management information systems to provide sufficiently accurate information in a timely manner to raise the level of administrative performance, and to determine the relationship of management information systems in evaluating the performance of employees at Tishreen University. The study concluded that administrative decision support systems, administrative information systems, and operational information systems have a role in improving the quality of administrative decisions at Tishreen University. Its reliance on information provided by administrative decision support systems, management information systems, and operational information systems. The study recommended that the university should increase its interest in administrative decision support systems because it will achieve quality in administrative decisions by achieving profits using the least resources, and providing services at lower costs.